2014
DOI: 10.7326/m14-0762
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Prevention in Women: Synopsis of the 2014 American Heart Association/American Stroke Association Guideline

Abstract: Description In February 2014, the American Heart Association/American Stroke Association released their first guideline focused on stroke prevention in women. This new guideline highlights unique risk factors for stroke in women, including oral contraception and hormone therapy, and pregnancy-associated disorders, such as preeclampsia, that may have long-lasting consequences on a woman’s health. It also addresses hypertension; atrial fibrillation; migraine headache with aura; and the epidemiology of types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…49 Similarly, evidence of an increased risk of stroke associated with type 2 diabetes in women has been included in American Heart Association/American Stroke Association guidelines for stroke prevention in women. 50 Our results show that AF is also a greater risk factor for death and cardiovascular disease in women than in men and extend these previous works showing that women experience the effects of some key risk factors for cardiovascular disease differently to men.…”
Section: Studysupporting
confidence: 89%
“…49 Similarly, evidence of an increased risk of stroke associated with type 2 diabetes in women has been included in American Heart Association/American Stroke Association guidelines for stroke prevention in women. 50 Our results show that AF is also a greater risk factor for death and cardiovascular disease in women than in men and extend these previous works showing that women experience the effects of some key risk factors for cardiovascular disease differently to men.…”
Section: Studysupporting
confidence: 89%
“…Women are affected by 40,000 more strokes annually than men, and represent approximately 56% of the 6.8 million stroke survivors in the United States. In addition, women are more likely to be older at the time of first stroke and have a lower quality of life post-stroke than their male counterparts, even after adjusting for other sex-specific variables (reviewed in Bushnell and McCullough, 2014; Gibson, 2013). Indeed, results of the Framingham Heath Study indicated that women were older at the time of stroke, have more comorbid disease at time of stroke, and tend to have more severe strokes with worse outcomes (Petrea et al, 2009).…”
Section: Estrogen Neuroprotection In Brain Injurymentioning
confidence: 99%
“…Current clinical guidelines recommend against the use of any kind of HT for primary or secondary prevention of stroke. The guidelines also emphasize that signifi-cant gaps persist in our understanding of the benefits and harms of HT, particularly with younger women who are in the early peri-menopausal and post-menopausal periods (Bushnell and McCullough, 2014; Bushnell et al, 2014). …”
Section: Estrogen Neuroprotection In Brain Injurymentioning
confidence: 99%
“…17 However, this should be compared with the risk of stroke in pregnancy, estimated to be approximately 34 per 100,000 deliveries. 18 Hypertension and smoking are the most important independent risk factors for both MI and ischaemic stroke. There is also evidence that migraine with aura, but not migraine without aura, increases the risk of ischaemic stroke and is a contraindication (UKMEC 4) to use of COCs.…”
Section: Principal Risksmentioning
confidence: 99%